TREN DAN DETERMINAN PENGANGGURAN TERDIDIK DI PROVINSI JAMBI. - Prihanto, Purwaka Hari (Jurnal Paradigma Ekonomika, 2012)
The objectives of this research are to analyse trend of the open unemployment and educated unemployment, also to examine the effect of wage rate, per capita income and employment of the educated unemployment in Jambi Province. This study was done in the Jambi Province, using the time series data from year 1990 to 2009, and to analyse the data used multiple regression with helped  SPSS program version 17. The results of study show that in periode of observation, the open unemployment rate in Jambi Province is 5.4 percent from total labor force, with 79.5 percent are educated unemployment. The regression model found that an educated unemployment determined by wage rate, per capita income, Formal sector employment and Informal sector employment. But partially,  the wage rate and Formal sector employment have negative effect on the educated unemployment, while per capita income and Informal sector employment have  positive effect on educated unemployment in Jambi Province.   Keywords: educated unemployment, wage rate, per capita income, Formal sector employment and Informal sector employment.